Plasma metabolome analysis identifies distinct human metabotypes in the postprandial state with different susceptibility to weight loss‐mediated metabolic improvements. Issue 10 (2nd May 2018) - Fiamoncini, Jarlei; Rundle, Milena; Gibbons, Helena; Thomas, E. Louise; Geillinger‐Kästle, Kerstin; Bunzel, Diana; Trezzi, Jean‐Pierre; Kiselova‐Kaneva, Yoana; Wopereis, Suzan; Wahrheit, Judith; Kulling, Sabine E.; Hiller, Karsten; et al.
ABSTRACT: Health has been defined as the capability of the organism to adapt to challenges. In this study, we tested to what extent comprehensively phenotyped individuals reveal differences in metabolic responses to a standardized mixed meal tolerance test (MMTT) and how these responses change when individuals experience moderate weight loss. Metabolome analysis was used in 70 healthy individuals. with profiling of ~300 plasma metabolites during an MMTT over 8 h. Multivariate analysis of plasma markers of fatty acid catabolism identified 2 distinct metabotype clusters (A and B). Individuals from metabotype B showed slower glucose clearance, had increased intra‐abdominal adipose tissue mass and higher hepatic lipid levels when compared with individuals from metabotype A. An NMR‐ based urine analysis revealed that these individuals also to have a less healthy dietary pattern. After a weight loss of ~5.6 kg over 12 wk, only the subjects from metabotype B showed positive changes in the glycemic response during the MMTT and in markers of metabolic diseases. Our study in healthy individuals demonstrates that more comprehensive phenotyping can reveal discrete metabotypes with different outcomes in a dietary intervention and that markers of lipid catabolism in plasma could allow early detection of the metabolic syndrome.—Fiamoncini, J., Rundle, M., Gibbons, H., Thomas, E. L., Geillinger‐Kästle, K., Bunzel, D., Trezzi, J.‐P., Kiselova‐Kaneva, Y., Wopereis, S., Wahrheit, J., Kulling, S. E., Hiller, K., Sonntag, D., Ivanova, D., van Ommen, B.., Frost, G., Brennan, L., Bell, J., Daniel, H. Plasma metabolome analysis identifies distinct human metabotypes in the postprandial state with different susceptibility to weight loss‐mediated metabolic improvements. FASEB J. 32, 5447–5458 (2018). www.fasebj.org